Autogestão e utopia na práxis dos movimentos sociais - Lins, Lucicléa Teixeira (2013)
Collective self-management is the subject of this thesis research that has as the main goal to understand the exercise of self-management in its historical path and in the educational praxis of the collective organization processes among workers. In its focus, the research comes to perceive the self-management, in its praxeological dynamics and its utopian perspective, seeing it through the praxis experienced in the wishes of those who dream another society. The research locus was done in seven rural settlements related to the MST Landless Rural Workers' Movement, PB, Brazil. The research started from the settlers experiences and organizational initiatives, pointing out their potentialities and limitations, as an educational process, consisting of a praxis that proposes to help in the economical and political emancipation of these collective subjects. The relevance of this study lies in trying to demonstrate the reality of the collective organization in these rural settlements, stressing the subjects management, how the self-management principle permeates their daily activities and practices. The theoretical-methodological approach of this study is characterized as a Qualitative Research, being led by the historical-dialectical method, and having as a theoretical support, the socialist thinkers approaches, and the Popular Education fundamentals. In its exposition, it presents theoretical and empirical data that confirm the thesis, in which it defends that there is an educational praxis in the workers collective organization that leads them to the self-management exercise. Throughout the research and its considerations, it can be perceived to exist in the self-management essence a praxis and an utopia that present themselves in various historical moments in socialist experiences, in their projects of organization of the working class, and in the raising of consciousness and autonomy of men and women. Self-management as history in the making characterizes by being negation to any centralization action, be it of economical or social order, thus having in the broad participation of people in the decision-making process its central focus